PENANAMAN NILAI-NILAI TOLERANSI PADA ANAK USIA DINI DI TK SEJAHTERA CITEKO KECAMATAN PLERED: THE CULTIVATION OF TOLERANCE VALUES IN EARLY CHILDHOOD AT TK SEJAHTERA CITEKO PLERED SUB-DISTRICT - Ambariah, Aam; Purnamasari, Rika; Kusnandar, Enan; Supendi, Dede (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
The main principle in shaping the identity of Indonesia as a multiracial country is the importance of values in life and social interaction, especially the virtue of tolerance.  The author highlights the need to build tolerance at a young age in this context through early childhood education, which focuses on establishing a learning environment that supports and encourages the development of children according to their age group. To characterize and explain the findings of the researchers, this study used descriptive qualitative research methodology.  This strategy is in accordance with the purpose of the study, which is to study how early childhood educators in TK Sejahtera Citeko in Plered Regency teach tolerance to their children.  In schools, tolerance is essential to create a morally upright social atmosphere. The needs of students, the educational environment, and existing resources should be considered when creating a lesson plan.  To encourage the growth of young students, educators must look for appropriate learning strategies and media.  The purpose of the evaluation is to find and correct deficiencies in the educational process.  According to the findings of the study, the tolerant character quality of early childhood students is formed when tolerance is regularly incorporated into daily learning activities.